Pengaruh Kepuasan Terhadap Niat Berkunjung Kembali Melalui Loyalitas Pelanggan di Destinasi Wisata Kota Tua, Jakarta - Filma Festivalia; M. Husen Hutagalung; Freddy Triono; Fifi Nofiyanti; Pricilia Johani Sakti (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2026)
This study aims to analyze the effect of customer satisfaction on revisit intention through customer loyalty among tourists visiting the Kota Tua Jakarta Tourism Destination. Kota Tua Jakarta is one of Indonesia’s prominent historical and cultural tourism destinations with strong tourist appeal, making it important for destination managers to understand the factors that encourage repeat visits. This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 150 tourists who had previously visited Kota Tua Jakarta using a purposive sampling technique. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results indicate that customer satisfaction has a positive and significant effect on customer loyalty as well as on revisit intention. Furthermore, customer loyalty also has a positive and significant effect on revisit intention. The mediation analysis reveals that customer loyalty significantly mediates the relationship between customer satisfaction and revisit intention. These findings suggest that enhancing tourist satisfaction can strengthen customer loyalty, which ultimately encourages tourists to revisit the destination. This study provides theoretical implications for the development of tourism marketing literature and practical implications for destination managers in improving customer loyalty and repeat visitation. Keywords: customer satisfaction, customer loyalty, revisit intention